Crosstalk between Exercise-Derived Endocannabinoidome and Kynurenines: Potential Target Therapies for Obesity and Depression Symptoms - Tiffany Wences Chirino; Edgar Rangel López; Alexandra Luna Angulo; Paul Carrillo Mora; Carlos Landa Solis; María Alejandra Samudio Cruz; Alim C. Fuentes Bello; Rogelio Paniagua Pérez; Juan Ríos Martínez; Laura Sánchez Chapul (MDPI AG, 2023)
The kynurenine pathway (KP) and the endocannabinoid system (ECS) are known to be deregulated in depression and obesity; however, it has been recognized that acute physical exercise has an important modulating role inducing changes in the mobilization of their respective metabolites-endocannabinoids (eCBs) and kynurenines (KYNs)-which overlap at some points, acting as important antidepressant, anti-nociceptive, anti-inflammatory, and antioxidant biomarkers. Therefore, the aim of this review is to analyze and discuss some recently performed studies to investigate the potential interactions between both systems, particularly those related to exercise-derived endocannabinoidome and kynurenine mechanisms, and to elucidate how prescription of physical exercise could represent a new approach for the clinical management of these two conditions.